Preference for Print or Electronic Book Depends on User’s Purpose for Consulting - Newton Miller, Laura (Evidence Based Library and Information Practice, 2014)
A Review of: Rod-Welch, L.J., Weeg, B.E., Caswell, J.V., & Kessler, T.L. (2013). Relative preferences for paper and for electronic books: Implications for reference services, library instruction, and collection management. Internet Reference Services Quarterly, 18(3-4), 281-303. doi: 10.1080/10875301.2013.840713 Abstract Objective – To determine patron format preference, perceived usability and frequency of e-book usage, and to study use and preference of e-reading devices. Design – Survey questionnaire. Setting – Large public research university in the United States of America. Subjects – 339 students, faculty, and staff members Methods – An anonymous 23-item survey was available in online and print formats. Print surveys were distributed in the lobby of the library and throughout various buildings on campus. A direct link to the online version of the survey was included in e-newsletters, on the library homepage, and on the library’s Facebook site. A definition of e-book was placed prominently at the beginning of the survey. Questions included information on preference of format (11), experiences using e-books (3), ownership of particular devices for reading e-books (1), attitudes regarding library purchase of e-books and readers (3), demographic information (4), and additional comments (1). Main Results – Of the 339 completed surveys, 79 were completed online and 260 in print. When asked about preference in format for reading, 79.6% of respondents preferred print books compared to 20.4% choosing e-books. If the library was purchasing a book to support class research and projects, 53.9% preferred print and 46.1% preferred electronic, but if the library purchased a book for leisure reading, 76% preferred print and 24% preferred electronic. In response to the question about how often they used e-books from the library, 50.1% of respondents never used library e-books, 21.1% used once per year, 20.8% monthly, 7.4% weekly and 0.6% daily. Of those who used e-books, 38.1% read only sections they needed, 31% searched keywords, 24.2% downloaded and printed pages to read later, 21.8% read the most relevant chapters, 17.1% skimmed the entire book and 14.2% read the entire book. If both formats were available, 25.1% felt that the library should purchase the print book, 16.7% the e-book, and 58.2% chose both formats. When asked about downloading e-books, 51.1% of respondents would use an e-book only if they could download it to a hand-held device. A majority of the respondents, 81.7%, felt that the library should provide e-readers for checkout if the library purchased e-books instead of print books. When asked which types of books they preferred to read in electronic format in an open-ended question, 22% preferred textbooks, 21% leisure reading, 18% research books, 15% other types, 6% journals, 5% reference books, and 3% anything. Regarding which types of books were preferred in print format, 42% preferred leisure reading, 21% other, 14% all, 11% textbooks, 6% research books, 2% no e-books, 2% journals and 2% reference books. Conclusion – Preference for book format (electronic or print) depends on the users’ purpose for reading the text. This will likely change over time, as users gain more familiarity and experience with e-books, and better support is provided from the library.